2012
DOI: 10.1161/circoutcomes.112.965251
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Apixaban Compared With Aspirin for Stroke Prevention in Atrial Fibrillation Among Patients Unsuitable for Warfarin

Abstract: Background-Compared with aspirin, apixaban reduces stroke risk in atrial fibrillation (AF) patients unsuitable for warfarin by 63% but does not increase major bleeding. We sought to determine the cost-effectiveness of apixaban versus aspirin. Methods and Results-Using the Apixaban versus Acetylsalicylic Acid to Prevent Stroke in Atrial Fibrillation PatientsWho Have Failed or Are Unsuitable for Vitamin-K Antagonist Treatment (AVERROES) trial and other studies, we constructed a Markov model to evaluate the costs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
7

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 34 publications
0
22
0
7
Order By: Relevance
“…Furthermore, limited data on the other new oral anticoagulants, rivaroxaban and apixaban, have been published recently. 75, 76 Even more data 77-79 and comparative efforts are awaited to facilitate optimal decision making in the antithrombotic management of AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, limited data on the other new oral anticoagulants, rivaroxaban and apixaban, have been published recently. 75, 76 Even more data 77-79 and comparative efforts are awaited to facilitate optimal decision making in the antithrombotic management of AF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulation with warfarin or the novel oral anticoagulants (NOACs) has been shown to reduce the risk of stroke in patients with AF by at least two-thirds [5,6]. A large number of economic analyses have recently been published assessing the cost effectiveness of NOACs, given their greater market cost; however, the vast majority of these studies do not use AFspecific cost data [7][8][9][10][11][12][13][14]. Even the UK National Institute of Health and Care Excellence (NICE) technology appraisals of the NOACs utilise stroke costs based on payment by results tariff, and prior systematic reviews that do not separate the costs of stroke according to AF status [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous cost-effectiveness studies have demonstrated that the drug is a dominant treatment option or cost-effective treatment option to aspirin in the USA and UK, respectively [11,12] but this evidence cannot be assumed to hold for other countries, as geographic variations in healthcare resource use and clinical practice suggest that findings may not be generalisable in this way [13]. Ultimately, assessing how closely health economic outcomes for different countries correlate with each other requires specific evaluations to be conducted for those territories.…”
Section: Introductionmentioning
confidence: 99%